An investigation into the phytoplankton package effect on the chlorophyll-a specific absorption coefficient in Barra Bonita reservoir, Brazil - Alcântara, Enner [UNESP]; Watanabe, Fernanda [UNESP]; Rodrigues, Thanan [UNESP]; Bernardo, Nariane [UNESP] (Taylor & Francis, 2016)
In this article, a possible phytoplankton package effect on the chlorophyll-a specific absorption coefficient (a*phy) is investigated. Two fieldworks were conducted in May and October 2014 in Barra Bonita (BB) reservoir. During the fieldworks, radiometric and water samples were obtained. From the radiometric data, the remote sensing reflectance (Rrs) were calculated and from the water samples the chlorophyll-a (chl-a) concentration, the phytoplankton absorption coefficient (aphy) and a*phy coefficient were obtained. The results show that for the first fieldwork (in May), the package effect was less perceived than in the second fieldwork (in October). In May, the package effect was more pronounced for the highest chl-a concentration (>200mgm−3) and for October all samples ranging from 263.20 to 797.80mgm−3 were effected. Due to this effect, the bio-optical model development in order to estimate the chl-a concentration in a eutrophic environment such as the BB reservoir will face higher errors when the chl-a concentration were higher than 300mgm−3.